2024
DOI: 10.1021/acs.chemmater.3c03108
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Mediated Synthesis of Lead-Free Cesium Titanium Bromide Double Perovskite: A Sustainable Approach

Emmanuel Reyes-Francis,
Carlos Echeverría-Arrondo,
Diego Esparza
et al.

Abstract: Theoretical studies have identified cesium titanium bromide (Cs2TiBr6), a vacancy-ordered double perovskite, as a promising lead-free and earth-abundant candidate to replace Pb-based perovskites in photovoltaics. Our research is focused on overcoming the limitations associated with the current Cs2TiBr6 syntheses, which often involve high-vacuum and high-temperature evaporation techniques, high-energy milling, or intricate multistep solution processes conducted under an inert atmosphere, constraints that hinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Recent investigations suggest that controlling the aqueous solution can also enhance environmental stability. For instance, Julián-López et al induced the formation of highly crystalline Cs 2 TiBr 6 using microwave radiation in polar solvents, not only reducing energy costs associated with perovskite production but also imparting exceptional stability to the resulting Cs 2 TiBr 6 . Konstantatos et al further enhanced Cs 2 TiBr 6 perovskite stability by post-treating it with SnBr 4 , adjusting the amount and reaction conditions to achieve optimal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations suggest that controlling the aqueous solution can also enhance environmental stability. For instance, Julián-López et al induced the formation of highly crystalline Cs 2 TiBr 6 using microwave radiation in polar solvents, not only reducing energy costs associated with perovskite production but also imparting exceptional stability to the resulting Cs 2 TiBr 6 . Konstantatos et al further enhanced Cs 2 TiBr 6 perovskite stability by post-treating it with SnBr 4 , adjusting the amount and reaction conditions to achieve optimal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little research has been done on vacancy-ordered perovskites for solar cells. Studies have shown that Cs 2 TiX 6 (X = Br and I) possesses multiple desirable attributes including good stability and high optical absorption coefficients in the visible light ranges. More recently, Zhao et al and Reyes-Francis et al, respectively, pointed out the ease of synthesis and high power conversion efficiency (PCE) of Cs 2 TiX 6 . , The impact of large exciton binding energy in Cs 2 TiX 6 may potentially be mitigated through atomic substitution or by changing the dielectric environment of the insulating organic layer. The aforementioned discussions suggest that Cs 2 TiX 6 holds the potential for use in solar cells. However, existing calculations and experiments have proven that both Cs 2 TiBr 6 and Cs 2 TiI 6 have some shortcomings that limit their further applications. , First, these two materials have quasi-direct bandgaps with indirect bandgaps between Γ (valence band maximum, VBM) and X (conduction band minimum, CBM), which are detrimental to their photovoltaic performance .…”
Section: Introductionmentioning
confidence: 99%